ANALISIS KINERJA KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL DI KOTA BATAM DALAM MEMBERIKAN PELAYANAN PEMBUATAN AKTA KEMATIANDAN AKTA KELAHIRAN - Nizam, Muhammad; Dompak, Timbul (LPPM Universitas Putera Batam, 2022)
The purpose of this study is to find out how the performance of the Batam City Population and Civil Registry Service in carrying out the service of making death certificates and birth certificates in Batam City. From the research carried out, there are data explaining the problems that occur in the service of making death certificates and birth certificates such as public complaints about inadequate services obtained by the community and also related to the quality of the performance of the Batam City Population and Civil Registry Office. How the implementation of the services provided must be able to achieve standards and produce effective and efficient performance in carrying out their duties. The method used in this research is quantitative research with a descriptive approach. Informants who were takenby researchers from the Batam City Population and Civil Registry Office and people who used the services of making death certificates and birth certificates. Researchers collect data from direct observation down to the field of interviews and documentation as well as information obtained from journals and books. The results obtained from this study can be concluded that the Batam City Population and Civil Registry Service has provided good services but there are some things that need to be improved, especially the awareness and responsibility of the resources that provide services. This can be found in Dwiyanto and Pasolong's theory of performance indicators, such as accountability, service quality, responsiveness, responsibility, and accountability